Pengaruh Biaya Operasional, Persediaan, Utang Usaha Dan Pendapatan Terhadap Laba Bersih Pada Masa Pandemi Covid-19 (Studi Kasus pada Rumah Sakit yang terdaftar di BEI tahun 2020-2022) - Herlina Kunthi Prabawati; Martinus Budiantara (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of operational costs, inventory, accounts payable and income on profits during the covid-19 pandemic. The population in this study are hospitals listed on IDX in 2020-2022. Of the seven hospitals listed on IDX, 3 hospitals can be used for research samples using purposive sampling method. The method used is quantitative research. In the multiple regression analysis performed, the result is the operational costs have a negative and signifikan effect on net profit. Inventory has a positive and significant effect on net profit and accounts payable has a positive and significant effect on net profit. Meanwhile, income has no significant effect on net profit.